Value of endoscopic ultrasonography for upper gastrointestinal stromal tumors: A single center experience - Ahmet AYDIN; Fatih TEKİN and Fulya GÜNŞAR and Adem GÜLER and Müge TUNÇYÜREK and Tankut İLTER (Turkish Journal of Gastroenterology, 2019)
-